3D printed antimicrobial PLA constructs functionalised with zinc- coated halloysite nanotubes-Ag-chitosan oligosaccharide lactate. (2nd January 2022) - Humayun, Ahmed; Luo, Yangyang; Elumalai, Anusha; Mills, David K.
ABSTRACT: S. aureus and S. epidermidis are the most common bacteria responsible for causing implant infections. We propose that 3D-printed antimicrobial biomedical devices are a rational solution for the prevention of infection. 3D printed polylactic acid (PLA) constructs were alkali-treated to increase hydrophilicity and functionalized using a suspension of Zinc/HNTs-Ag-Chitosan Oligosaccharide Lactate (ZnHNTs-Ag-COS). PLA constructs were analyzed using scanning electron microscopy and Fourier-transform infrared spectroscopy (FTIR). The antimicrobial potential was assessed using agar diffusion and biofilm assays. The surface of 3D printed PLA constructs were chemically modified to increase hydrophilicity and suspensions of COS-ZnHNTs-Ag were adsorbed on the construct surface. Surface adsorption of ZnHNTs-Ag-COS on PLA printed constructs was determined to be a function of relative pore size. Morphological surface characterization confirmed the presence of the suspension coatings on the constructs, and FTIR analysis confirmed the presence of COS-ZnHNTs-Ag coatings. Growth inhibition studies validated the antimicrobial properties of PLA constructs.